La transición al capitalismo en el diálogo literario de Joseph de la Vega: Confusión de confusiones (1688) - Jesús Gómez (Mélanges de la Casa de Velázquez)
Still barely studied from a literary point of view, Joseph de la Vega’s dialogue Confusion of Confusions is part of the development of baroque writing. At the same time, it derives from the argumentative process associated with the conventions of the dialogic genre from which I will consider the characterization of its three interlocutors. The dialogical mimesis allowed the dialogist to incorporate the adverse reactions of two novel investors, the subtle philosopher and the circumspect merchant, to the stock exchange crisis of 1688. The clever shareholder, on the other hand, justifies, as his main interlocutor, the speculative risk that governs the Amsterdam stock exchange on which the economic boom of Dutch capitalism is based in contrast with the characteristic values of courtly society.